Computerised system to rate junior athletes' psycho-emotional stability in team and individual sport disciplines - Ismailova, N. I.; Tsagarelli, Y. A.; Shumikhin, S. L. (Theory and Practice of Physical Culture, 2017)
Top priority in the training system design is given to the junior athletes` mental stability and self-control under sport-specific emotional pressures as they are considered one of the key prerequisites for progress and competitive accomplishments. These fitness components are collectively referred to as the psycho-emotional stability that was rated and analysed in the study using the computerised Activation-meter AT-9K system in application to junior team and individual athletes. Every sport is known to develop a range of sport-specific individual mental qualities that may be rated by the Cattel`s 16 Personality Factor Questionnaire. Objective of the study was to rate and analyse the junior athletes` (n=62) psycho-emotional stability and personality qualities important for the relevant team and individual sports. The subjects engaged in team sports were tested with well-developed self-control, purposefulness, discipline and high psycho-emotional stability rates. These sport-specific qualities help them keep under control the mental and emotional stresses and maintain the optimal emotional balance for high performance and competitive success. The subjects engaged in individual sports were found to rely on luck and show a fair self-confidence and independence in their judgements and behaviours. Their psycho-emotional stability rates are not high enough and, hence, they are more vulnerable to tension and prone to emotional outbursts, and this fact needs to be taken into account in the sport excellence process design.